2004
DOI: 10.1161/01.cir.0000140980.61294.4d
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight Is Associated With Higher Adult Total Cholesterol Concentration in Men

Abstract: Background-The majority of studies investigating the association between birth weight and adult total cholesterol (TC) concentration have been small and underpowered: not surprisingly, the findings have been inconsistent. We aimed to determine whether birth weight predicted adult TC in a large sample population. Methods and Results-Between 1994 and 1996, 132 000 British Telecom employees undertook voluntary occupational health screening. Birth weight and lifestyle factors were self-reported; TC concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 22 publications
6
56
2
1
Order By: Relevance
“…After excluding these subjects, mean birth weights were comparable to figures observed in the 1958 cohort (males: 3.43 kg versus 3.40 kg in the 1958 British cohort; females: 3.26 kg versus 3.26 kg). 12 Furthermore, birth weight category distributions and association between birth weight and adult height 11 were similar to those observed in the 1958 British cohort. 12,13 Therefore, the following results are for volunteers with birth weights between 800 and 5000 g. However, the results were similar when all of the data were included or participants with a high likelihood of having been born prematurely (birth weight Ͻ1500 g) were excluded.…”
Section: Validating Recalled Birth Weightssupporting
confidence: 55%
See 2 more Smart Citations
“…After excluding these subjects, mean birth weights were comparable to figures observed in the 1958 cohort (males: 3.43 kg versus 3.40 kg in the 1958 British cohort; females: 3.26 kg versus 3.26 kg). 12 Furthermore, birth weight category distributions and association between birth weight and adult height 11 were similar to those observed in the 1958 British cohort. 12,13 Therefore, the following results are for volunteers with birth weights between 800 and 5000 g. However, the results were similar when all of the data were included or participants with a high likelihood of having been born prematurely (birth weight Ͻ1500 g) were excluded.…”
Section: Validating Recalled Birth Weightssupporting
confidence: 55%
“…As reported previously, 11 comparison of birth weight distribution with the 1958 British cohort, a cohort with similar mean age but that only used birth weight derived from hospital records, 12 suggested that birth weights Ͻ800 g (6 participants, 0.02%) and Ͼ5000 g (163 participants, 0.6%) may have been misreported. After excluding these subjects, mean birth weights were comparable to figures observed in the 1958 cohort (males: 3.43 kg versus 3.40 kg in the 1958 British cohort; females: 3.26 kg versus 3.26 kg).…”
Section: Validating Recalled Birth Weightsmentioning
confidence: 73%
See 1 more Smart Citation
“…Perhaps the best example of this association is the link between intrauterine growth restriction (IUGR) and the metabolic syndrome in adulthood, expressed in terms of insulin resistance (1,2), type 2 diabetes (1), hypertension (3,4), an altered lipid profile (5,6), obesity (7)(8)(9)(10), and cardiovascular disease (11,12). The thrifty phenotype hypothesis of Hales and Barker (13) proposes that low birth weight and associated long-term insulin resistance are adaptive if food supplies are scarce and likely to remain so over time.…”
mentioning
confidence: 99%
“…Além disso, em achados subseqüentes, esses e outros pesquisadores demonstraram que o baixo peso ao nascer se associava a um padrão alterado de lipídeos plasmáti-cos 12 , redução da densidade óssea 13 , respostas ao estresse diferenciadas 14 , artérias menos elásticas 15 , padrões de secreção hormonal específicos 16,17 e maior incidência de depressão 18,19 . Essas observações geraram a "hipótese do fenótipo poupador" (thrifty phenotype hypothesis), a qual propõe que o feto é capaz de se adaptar a um ambiente intra-uterino adverso otimizando o uso de suprimentos energéticos reduzidos, no sentido de garantir sua sobrevivência.…”
Section: Modelos Causaisunclassified